An experimental study on the local buckling strength of an SBHS700 stub column with cruciform section: With an overview of the mechanical properties of SBHS700. Issue 2 (2nd May 2019) - Nie, Jing; Sugimoto, Hikaru; Ono, Kiyoshi; Miyashita, Takeshi; Matsumura, Masahide; Okada, Seiji
Abstract: Kurita‐Albrecht Young Engineers Award 2018 – Steel Recently, SBHS (Steels for Bridge High‐Performance Structure) has been introduced in Japan because of its remarkable mechanical properties. The main features of SBHS are high yield strength, improved toughness and weldability, which are superior to conventional steel materials at the corresponding tensile strength grades. In this study, these material properties of SBHS were compared with conventional steel materials through experimental studies as well as the Japanese design specifications. The main focus of this paper is the evaluation of the local buckling strength of two SBHS700 stub columns, each with cruciform section through compression tests. The load‐displacement relationship, strain bifurcation related to plate buckling and out‐of‐plane deformation are discussed. Two test specimens with different width‐to‐thickness ratio parameters R R are compared. As the results indicate, for the specimen having a larger R R, an abrupt decrease in load was observed after the peak load, whereas the decrease in load for the specimen with a smaller R R proceeded gradually after the peak load with a much larger vertical displacement. In terms of local buckling strength, it was found to be possible to evaluate the SBHS700 stub column with cruciform section based on the existing ultimate strength curves.